2021
DOI: 10.1007/s13679-021-00449-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Self-quarantine and Weight Gain Risk Factors in Adults

Abstract: Purpose of Review The COVID-19 pandemic is associated with weight gain in certain individuals. This review highlights the risk factors for weight gain during COVID-19 self-quarantine in adults. Recent Findings Among those who have gained weight during COVID-19 self-quarantine, self-reported body weight has increased between .5 and 1.8 kg (± 2.8 kg) after just 2 months of quarantine. Identified risk factors for weight gain during COVID-19 self-quarantine are the following: increased sedentary behaviors, decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
74
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 84 publications
10
74
2
Order By: Relevance
“…Reviews from the initial months of the pandemic indicate an overall trend for increased food consumption [7,53], with increased FV consumption in some individuals, but also increased HFSS foods consumption in others [6,54]. In particular, increased snacking has been identified during the start of the pandemic [18,[54][55][56], with a greater proportion of individuals increasing than decreasing HFSS snacks intake [18,54], as with our results.…”
Section: In Context Of Covid-19 Researchsupporting
confidence: 86%
See 1 more Smart Citation
“…Reviews from the initial months of the pandemic indicate an overall trend for increased food consumption [7,53], with increased FV consumption in some individuals, but also increased HFSS foods consumption in others [6,54]. In particular, increased snacking has been identified during the start of the pandemic [18,[54][55][56], with a greater proportion of individuals increasing than decreasing HFSS snacks intake [18,54], as with our results.…”
Section: In Context Of Covid-19 Researchsupporting
confidence: 86%
“…Individuals tend to consume more palatable and less healthy foods during stressful life periods [62]. A greater decline in mental health or increased stress, boredom or anxiety from COVID-19 has been associated with increased ultra-processed, HFSS foods intake, decreased FV intake and using snacking as a coping mechanism [9,14,32,55,56,[63][64][65]. The increased HFSS snacking at the start of the pandemic may reflect such maladaptive coping mechanisms [63,66].…”
Section: In Context Of Covid-19 Researchmentioning
confidence: 99%
“…In contrast, 18% of the respondents reported that they lost more weight than they wanted during the COVID-19 pandemic [ 2 ]. In these studies, and others during the pandemic, a key finding was that those who had higher stress, were obese or overweight, younger or with lesser incomes, or those who were racial/ethnic minorities were significantly more likely to report unhealthy eating practices [ [6] , [7] , [8] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…One study of 268 American adults who provided both survey and wearable device data found a 21% decrease for walking and a 46% decrease for moderate-intensity exercise [ 15 ]. Irrespective of the assessment methods, but similar to diet behaviors, higher physical activity declines were noticed across several studies among racial/ethnic minorities, individuals of lower socioeconomic status, those with greater weight or less physical activity before the pandemic, and those with greater stress [ 2 , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the pandemic appears to be increasing obesity levels [67], a phenomenon that could prompt public health officials to conceive of preventive interventions. individuals who have undergone bariatric surgery [71]; vegetarians [72]; and alcoholics [73].…”
Section: Discussionmentioning
confidence: 99%